2021
DOI: 10.3390/ijms22020621
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Columbianadin, a Bioactive Coumarin Derivative, in Perturbing Transient and Persistent INa

Abstract: Columbianadin (CBN) is a bioactive coumarin-type compound with various biological activities. However, the action of CBN on the ionic mechanism remains largely uncertain, albeit it was reported to inhibit voltage-gated Ca2+ current or to modulate TRP-channel activity. In this study, whole-cell patch-clamp current recordings were undertaken to explore the modifications of CBN or other related compounds on ionic currents in excitable cells (e.g., pituitary GH3 cells and HL-1 atrial cardiomyocytes). GH3-cell expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 43 publications
6
19
0
Order By: Relevance
“…In these whole-cell current recordings, the examined cell was voltage-clamped at −50 mV and a set of upright isosceles-triangular ramp pulses ranging between −100 and +50 mV with varying durations at a rate of 0.05 Hz was gingerly applied to it through digitalto-analog conversion (Figure 6A). In accordance with previous observations [25,38], when GH 3 cells were exposed to 10 µM Tef alone, the amplitude of I Na(P) at high or low threshold respectively activated by the upsloping (forward, ascending) or downsloping (backward, descending) end of upright triangular ramp voltage was raised and a striking figure-ofeight hysteresis (i.e., ∞) in the instantaneous I-V relationship of I Na(P) was concurrently revealed (Figure 6B,C). For example, as the isosceles-triangular ramp pulse with a duration of 0.8 s (or ramp speed of ±0.38 mV/ms) was applied, in the presence of 10 µM Tef, the peak I Na(P) amplitude measured at the level of −30 mV (i.e., high-threshold I Na(P) ) during the ascending phase of triangular ramp pulse was conceivably raised to 62 ± 9 pA (n = 7, p < 0.05) from a control value (measured at the same level of membrane potential) of 21 ± 4 pA (n = 7).…”
Section: Augmented Amplitude and Hysteresis By Tef Of Persistent Na + Current (I Na(p) ) Attenuated By Esaxsupporting
confidence: 93%
See 2 more Smart Citations
“…In these whole-cell current recordings, the examined cell was voltage-clamped at −50 mV and a set of upright isosceles-triangular ramp pulses ranging between −100 and +50 mV with varying durations at a rate of 0.05 Hz was gingerly applied to it through digitalto-analog conversion (Figure 6A). In accordance with previous observations [25,38], when GH 3 cells were exposed to 10 µM Tef alone, the amplitude of I Na(P) at high or low threshold respectively activated by the upsloping (forward, ascending) or downsloping (backward, descending) end of upright triangular ramp voltage was raised and a striking figure-ofeight hysteresis (i.e., ∞) in the instantaneous I-V relationship of I Na(P) was concurrently revealed (Figure 6B,C). For example, as the isosceles-triangular ramp pulse with a duration of 0.8 s (or ramp speed of ±0.38 mV/ms) was applied, in the presence of 10 µM Tef, the peak I Na(P) amplitude measured at the level of −30 mV (i.e., high-threshold I Na(P) ) during the ascending phase of triangular ramp pulse was conceivably raised to 62 ± 9 pA (n = 7, p < 0.05) from a control value (measured at the same level of membrane potential) of 21 ± 4 pA (n = 7).…”
Section: Augmented Amplitude and Hysteresis By Tef Of Persistent Na + Current (I Na(p) ) Attenuated By Esaxsupporting
confidence: 93%
“…As the ramp speed decreased, the area of such hysteretic loop progressively reduced. Therefore, findings from the present observations revealed that the triangular pulse-induced I Na(P) was observed to undergo hysteretic change in the voltage dependence found in GH 3 cells [29,30,38].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In the first stage of measurements, we kept cells immersed in a Ca 2+ -free Tyrode’s solution containing 0.5 mM CdCl 2 , the composition of which was stated in Materials and Methods, and we filled up the pipette by using the Cs + -containing solution. As the whole-cell configuration was firmly established, we voltage-clamped the tested cell at the level of −80 mV and a brief step depolarization to −10 mV was delivered to activate I Na with a rapid activation and inactivation [ 23 , 25 , 26 ]. Of interest, one minute after cells were continually exposed to aPO , the peak amplitude of I Na was progressively increased, and the concomitant inactivation time course of the current slowed ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…The statistical analyses were undertaken by ANOVA-2 for repeated measures, p (factor 1, groups among data ken at different interpulse intervals) < 0.05, p (factor 2, groups between the absence and presence of aPO) < 0.05, p (interaction) < 0.05, followed by post-hoc Fisher's least-significant difference test, p < 0.05). Tef, a type-I pyrethroid insecticide, was reported to be an activator of I Na [23][24][25]27], Ran is recognized as a late I Na blocker as well as an inhibitor of NOX activity [26,[28][29][30], and RFM, known to be an antiepileptic agent, was previously demonstrated to perturb I Na inactivation [31,32]. For these reasons, we further examined and then compared the effects of these agents on peak I Na identified in GH 3 cells.…”
Section: Comparison Among Effects Of Apo Tefluthrin (Tef) Tef Plus Apo Apo (Rfm) and Apo Plus Ranolazine (Ran) On The Peak Amplitude Of Imentioning
confidence: 99%